Trends in Ezetimibe Prescriptions as Monotherapy or Fixed-Dose Combination in Germany 2012–2021 - Katzmann, Julius L.; Kieble, Marita; Enners, Salka; Böhm, Michael; Mahfoud, Felix; Laufs, Ulrich; Schulz, Martin (Frontiers in Cardiovascular Medicine, 2022)
Aims: Addition of ezetimibe to statin therapy is recommended by current guidelines when low-density lipoprotein cholesterol (LDL-C) targets are not achieved with statin monotherapy. Fixed-dose combinations (FDC) improve medication adherence and facilitate risk factor control. We assessed prescription trends of ezetimibe as monotherapy or FDC with statins. Methods: Data from the German Institute for Drug Use Evaluation (DAPI) containing dispensing data of >80% of community pharmacies were analysed. Prescriptions over time of lipid-lowering agents at the expense of the statutory health insurance (SHI) were extrapolated to all SHI-insured persons, representing approximately 88% of the total German population. Drug utilization was expressed as defined daily doses per 1,000 SHI-insured persons per day (DID). Results: Of all lipid-lowering drug prescriptions in 2021, 91.2% were statin monotherapy. Ezetimibe was prescribed as monotherapy or FDC with statin in 4.4% and 2.9%, respectively. DID steadily increased for statin (69%) and ezetimibe (424%) monotherapies between 2012 and 2021. In contrast, statin-ezetimibe FDC prescriptions exhibited only a minor increase (29%). The proportion of statin-ezetimibe FDC among all statin prescriptions was stable over time at approximately 3%. FDC prescription rates by specialists were higher compared to general practitioners and varied considerably between geographic areas. Conclusion: Combination lipid-lowering therapy is prescribed to a minority of patients. Prescriptions of ezetimibe as monotherapy increased to a much greater extent than statin-ezetimibe FDC. Considering the low proportion of patients achieving their LDL-C target and improved adherence to FDC compared to separate pills, statin-ezetimibe FDC may be utilized to improve the management of dyslipidaemia.